Politics of a church at war: Maronite Catholicism in the Lebanese Civil War - Henley, ADM (Taylor and Francis, 2008)
Intrinsically linked to the power-sharing Maronite Catholic community, and historically tied to the fate of Lebanon, the Maronite Church was deeply involved in, and affected by, the 1975–90 Civil War. This study seeks to understand the changing role of the patriarchs during this time, recognizing that their relative withdrawal from politics – declining to assert the temporal authority of their predecessors – does not equate to the marginalization of the church as a whole. Analysing the internal politics of the church as a microcosm of the community's struggle, the study examines in detail a threefold relationship between the patriarchate, the papacy, and the monastic orders.